(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Currently, the choice of medications for the treatment of non-specific ulcerative colitis and the determination of its duration remain a controversial issue. When treating ulcerative colitis, 5-aminosalicylic acid derivatives (mesalazine) are used as a first-line therapy. The choice of a drug and its form requires an individual approach, and when making a decision about therapy, it is necessary to take into account the duration of the inflammatory process, the activity of the inflammatory process, and the level of drug safety.